Self-Standing Nanomembranes of Super-Tough Plastics - Funahashi, Yasuyoshi (Langmuir : the ACS journal of surfaces and colloids, 2022)
Nanomembranes are effective coating materials for protecting substrates from external stimuli; however, they are generally not self-standing owing to their low mechanical toughness. Self-standing nanomembranes would be an innovative development in the field of nanotechnology including miniaturized devices. In this study, self-standing nanomembranes were developed by spin-casting supertough polyamides over dimethylformamide solution. The polyamides were synthesized by the polycondensation of two derivatives of 4,4'-diamino-α-truxillic acid (4ATA) with slightly bent diphenylcyclobutane in the core. Mechanical evaluation of the 4ATA polyamides having an appropriate composition of aliphatic diacids revealed a high strain-energy density of 231 MJ m-3 at its maximum, which is significantly tougher than spider silk. The nanocoats with a thickness of several hundred nanometers showing interference fringes were able to be peeled off the glass substrate without breaking, owing to its ultrahigh toughness. The self-standing nanomembrane would be applied to flexible devices in the future